Farm to school of Park County : a journey from program to nonprofit (C) - Cates, Karen L., (SAGE business cases, 2019)
The third in a four part case series, this case describes how Farm to School's board developed a strategic plan and establishes committees. However, the board members and leaders start to feel fatigue in the face of the demands of a startup organization, leading to questions about what is truly strategic and how work will be completed.